What would change in Brazil's practice with the adoption of an investor-state dispute settlement mechanism in its investment agreements? - Monebhurrun, Nitish (2019)
Brazil has always rejected investor-State arbitration as a means of dispute settlement and its recent Agreements on Cooperation and Facilitation of Investments confirms this choice. Nearly seven decades of investment arbitration practice has not convinced Brazil nor has it inflected its position on the matter. This means that should Brazilian investors face a legal problem in the host States with which Brazil has signed an investment agreement, they will, to some extent, be powerless as far as international juridical recourse is concerned in that the Brazilian investors will not be able to sue these States directly before an international arbitral tribunal. This is a disadvantage if compared to the direct access to international arbitration given by the investment agreements of other States to private investors. This article will examine the question of what would effectively change in the Brazil’s practice should the investor-State arbitration be incorporated in the Brazilian investment agreements as a dispute settlement mechanism. This would enable the Brazilian government and negotiators to have a comparative factor and measure the pros and cons of inserting an investor-State arbitration clause in the investment agreements. The article concludes that if the arbitration clause is technically and cautiously drafted, there is no need to fear investor-State arbitration.